Impacts of resistant starch and the enzyme transglutaminase on the technological characteristics of spaghetti (Research, Society and Development, 2020)
The use of resistant starch in new food products is increasing due to the health benefits associated with fiber intake. However, its use in products such as pasta is limited because it weakens the gluten network. One way to solve this problem is by adding enzyme transglutaminase into the formulation. The objective of this study was to evaluate the influence of resistant starch (RS) and transglutaminase (TG) on spaghetti cooking characteristics, texture, color and protein solubility using a central composite rotational design of two independent variables (x1 = RS 0 to 20 %; x2 = TG 0.2 to 1.0 %). The main dependent variables studied were resistant starch, instrumental color, cooking and texture characteristics and protein solubility. The results were analyzed using Response Surface Methodology, which demonstrated that RS and TG influenced the product quality, being statistically significant (p